WANITA KARIR DALAM PANDANGAN ISLAM - Shodiq (IAIN Surakarta), Fajar (Manajemen Bisnis Syariah, 2011)
Career woman received less attention in the past. It is because the cultural or religion reason considered as the “inhibition” of woman working outside home. As the time progresses, the woman has begun to attend the education as high as the man, and started to develop the capability she has in all aspects, whether in economic or social area. However, there is still a tickling question, “is woman permitted to work outside home in Islam, to earn bread along with the man to help her household economy, and to play a role in building her nation? In fact, Islam has appreciated the woman who develops career and integrates in synergy between the world and the hereafter affairs without forgetting her duty as housewife who taking care of her family, religion, her self and her ethics as well as noble moral for the woman working or developing career outside home. The example in the past in Rasulullah SAW proves the toughness of the woman who developed career and who fought along with strong and bravery Islamic soldiers, who could give benefit to herself and other human beings.   Keywords: Women, Career, Work